Frequency and Diversity of Congenital Heart Disease in Children in Northern Iran - Mohsen Ebrahimi; Hassan Esmaeili (Golestan University Of Medical Sciences, 2022)
Background and objectives: One of the leading causes of neonatal death is congenital abnormalities. The most prevalent congenital condition in the world is congenital heart disease (CHD), which affects around one-quarter of all live newborns. Given the significance of CHD, this study aimed to evaluate the prevalence of pediatric congenital heart disease and its variants in Gorgan, northern Iran. Methods: This descriptive cross-sectional survey examined 1,416 patients suspected of having CHD who had been referred to the Taleghani Hospital in Gorgan from 2014 to 2016. Results: The most common CHDs were ventricular septal defect (44.92%), atrial septal defect (23.73%), and patent ductus arteriosus (18.63%). Males had a higher rate of transposition of great arteries. Conclusion: The present study expands our knowledge of the regional frequency of CHD types in children with no acquired heart diseases in Gorgan, Iran. Moreover, ventricular septal defect is the most common type of CHD among patients, mainly males.